Methods of optimal subbands signal processing - Eugene G. Zhilyakov; S. P. Belov (Наука. Инновации. Технологии)
The approach has been developed for analysis and synthesis of signals based on variational principles, formed in the language of the frequency representation , which allows for adequacy in terms of reflecting the physical nature of tasks: determining the exact pro-portion of the energy values of the analyzed signal at predetermined frequency intervals; optimal filtering resulting vectors derived components are determined only by the energy of the signal in the relevant frequency interval; generation of signals with a minimum of leakage of energy outside the selected frequency band.